Find the equations of the tangents to the circlex^2 + y^2 - 4x + 6y - 12 = 0 which are parallel to
3x-y+4=0
Answers
Answered by
6
EXPLANATION.
→ Equation if tangent to the circle
x² + y² - 4x + 6y - 12 = 0.
→ parallel to the line = 3x - y + 4 = 0
→ x² + y² + 2gx + 2fy + c = 0 → general equation
of the circle.
→ compare the equation with general equation.
→ centre = ( -g, -f)
→ centre = ( 2,-3)
→ radius = √g² + f² - c
→ √ (2)² + (-3)² - (-12)
→ √ 4 + 9 + 12
→ √ 25 = 5
→ Tangent parallel to the line → 3x - y + 4 = 0
→ 3x - y + c = 0
→ equation of tangent.
→ 3x - y + 13= 0 and 3x - y - 13 = 0.
Answered by
85
Equation if tangent to the circle
x² + y² - 4x + 6y - 12 = 0.
→ parallel to the line = 3x - y + 4 = 0
→ x² + y² + 2gx + 2fy + c = 0 → general equation
of the circle.
→ compare the equation with general equation.
→ centre = ( -g, -f)
→ centre = ( 2,-3)
→ radius = √g² + f² - c
→ √ (2)² + (-3)² - (-12)
→ √ 4 + 9 + 12
→ √ 25 = 5
→ Tangent parallel to the line → 3x - y + 4 = 0
→ 3x - y + c = 0
→ equation of tangent.
→ 3x - y + 13= 0 and 3x - y - 13 = 0
x² + y² - 4x + 6y - 12 = 0.
→ parallel to the line = 3x - y + 4 = 0
→ x² + y² + 2gx + 2fy + c = 0 → general equation
of the circle.
→ compare the equation with general equation.
→ centre = ( -g, -f)
→ centre = ( 2,-3)
→ radius = √g² + f² - c
→ √ (2)² + (-3)² - (-12)
→ √ 4 + 9 + 12
→ √ 25 = 5
→ Tangent parallel to the line → 3x - y + 4 = 0
→ 3x - y + c = 0
→ equation of tangent.
→ 3x - y + 13= 0 and 3x - y - 13 = 0
Anonymous:
Nice ^^"
Similar questions
English,
4 months ago
Social Sciences,
4 months ago
Computer Science,
9 months ago
Physics,
9 months ago
Chemistry,
1 year ago
Science,
1 year ago